Hysteria to conversion disorders: Babinski's contributions - Marleide da Mota Gomes; Eliasz Engelhardt (Arquivos de Neuro-Psiquiatria)
The main objective of this paper is to present the importance of hysteria on Babinski's oeuvre, and the conceptions of pithiatism from Babinski until the one of conversion disorder. Babinski gave a mental basis for hysteria in the place of Charcot's encephalopatic one, and several important semiotic tools to differentiate organic from hysterical manifestations based on studies from 1893-1917/8. His teachings were spread worldwide, and in Brazil they were also appreciated in the work on hysteria by Antonio Austregesilo, the first Brazilian neurology chairman. The neurobiological basis of hysteria conceived by Charcot is nowadays reappraised, and Babinski's neurosemiological contribution is everlasting. The patients believed to be hysterical, and the two outstanding neurologists, Charcot and Babinski, gave support for the development of the modern neurology.